A HYBRID MODEL OF AN ESP COURSE DESIGN FOR NURSING STUDENTS - Nina Herlina, - (2022)
The study reports the results of a design-based research on a hybrid model of an ESP course for nursing students. Low attendance, lack of relevant printed medical English books, and ignorance of technology for learning were all expected to be addressed by the model at one of Cirebon's institutes of health science. This study focuses on four objectives: first, investigating what ESP course nursing students require to meet the healthcare industry expectations; second, specifying a hybrid model of an ESP course design that diverges traditional instructions; third, designing, developing, and refining the intervention design; fourth, discovering the effects on the ESP teaching, learning, and students' English proficiency. The blended learning framework, the language-centered approach in ESP course design and SKKNI (Standar Kompetensi Kerja Nasional Indonesia) or occupational competency standards, underpinned the study. Informed exploration, enactment and evaluation phases of integrative learning design framework were used. Representing state and private hospitals, 135 participants were included consisting of nursing students, ESP teachers, nursing educators, nursing instructors and users of nurses. Themes emerged from document analysis, needs analysis, field notes, student reflections, questionnaires, and interviews. Descriptive statistics and non-parametric tests were used to analyze quantitative data from success criteria and TOIEC scores. It is recommended that ESP course be tailored to job scenarios as healthcare providers. The intervention design specifies a hybrid ESP course using online and onsite modes with synchronous and asynchronous elements. A mismatch in TOEIC score changes implies minor evidentiary difference, The SKKNI has distinct competency units for different industries, therefore, this study may not be applied to other ESP settings. Accordingly, research on hybrid learning in other disciplines is warranted. Keywords: English for Specific Purposes, Hybrid learning, SKKNI.